(3GdYbhO GdLhgQjI aj Md CdaGX GdCRgQjIs - (3Rjf GdOjf efUhQ SHW fGUQ GdOjf GdWHdGhjs; (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO,J (B905 (3g` s
(3ChdgG (B:s
(3CeG HYO, agPG TQM dWja, hJMQjQ TQja, hVYJg Ydi GdebOeI GdCRgQjI aj Yde GdYQHjI GdefShHI s
(3BNQgG (B:s
(3dCf GdhShSI UGOQI ef GdbHjdjf Ydi hLg jdjb Hcd efgeG CLGRfG Gddg SHMGfg hJYGdi ef Pdc s
(3fSNI KGfjI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3HChdgG JedcGJ CbOegG (B1128(3g`s
(3hHgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs